2012
DOI: 10.1177/1753193412439673
|View full text |Cite
|
Sign up to set email alerts
|

Management of severe Dupuytren’s contracture of the proximal interphalangeal joint with use of a central slip facilitation device

Abstract: Thirty-eight fingers in 27 patients with Dupuytren's contracture of the proximal interphalangeal joint (PIPJ) in excess of 70° were treated using a staged technique. The first stage involved applying a mini external fixator across the PIPJ for continuous extension over 6 weeks with intensive hand therapy to maintain mobility of the joint and help correct the deformity. Twice weekly during hand therapy sessions the tension of the elastic band across the mini ex-fix was increased, allowing that full active flexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 16 publications
(17 reference statements)
1
21
1
Order By: Relevance
“…All patients achieved full correction of the deformity over a short period of time, even in patients with recurrent Dupuytren disease. It is 'low tech', does not require bulky and expensive external fixators, and can be applied without fluoroscopic guidance or regional anesthesia, unlike some other methods described (3)(4)(5)7). We believe that this modification offers the advantages of the method described by White et al (7), while being easier and less resource intensive that the original description.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…All patients achieved full correction of the deformity over a short period of time, even in patients with recurrent Dupuytren disease. It is 'low tech', does not require bulky and expensive external fixators, and can be applied without fluoroscopic guidance or regional anesthesia, unlike some other methods described (3)(4)(5)7). We believe that this modification offers the advantages of the method described by White et al (7), while being easier and less resource intensive that the original description.…”
Section: Discussionmentioning
confidence: 88%
“…White et al (7) described an additional method for correcting these deformities, and we use a modification of this method. In their published study, two mini-external fixators are applied under fluoroscopic guidance to the dorsum of the middle and proximal phalanges, and elastic (rubber) bands are passed between these two constructs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An external fixator is a technique that has been proposed as a potential method of correcting PIP flexion contractures and can be used either before or after the formal Dupuytren's surgery [101].…”
Section: Recurrencementioning
confidence: 99%
“…Eleven therapeutic single cohort studies were identified, but are not discussed further in this article. Most of these concerned techniques on which data has been previously published such as needle fasciotomy and external fixator devices [9][10][11], although there are also some novel techniques such as lipofilling in needle fasciotomy [12]. However, without comparison with a control group these more novel techniques should be considered preliminary in nature.…”
Section: Level IV Evidencementioning
confidence: 99%